Prechemotherapy antimullerian hormone, age, and body size predict timing of return of ovarian function in young breast cancer patients. Issue 23 (31st July 2014) - Su, Hui‐Chun Irene; Haunschild, Carolyn; Chung, Karine; Komrokian, Sara; Boles, Sarah; Sammel, Mary Dupuis; DeMichele, Angela
<x xml:space="preserve">Abstract</x> BACKGROUND Endocrine measures of ovarian reserve before breast cancer treatment may predict postchemotherapy ovarian function, providing prognostic information at the time of cancer diagnosis. The objectives of this study were 1) to determine whether prechemotherapy levels of antimullerian hormone (AMH), follicle‐stimulating hormone (FSH), and inhibin B (inhB) are associated with the return of ovarian function after chemotherapy and 2) to generate a prognostic score for ovarian recovery in young women with breast cancer. METHODS A prospective cohort study recruited 109 participants (median age, 39 years; age range, 23‐45 years) before chemotherapy from 2 breast clinics and followed them longitudinally. By using time‐to‐event analysis, the authors tested the association between prechemotherapy AMH, FSH, and inhB levels and the time to return of ovarian function, as measured by menstrual pattern. RESULTS After a median follow‐up of 163 days (range, 4‐1009 days) after chemotherapy, 62 participants (57%) experienced return of ovarian function. In adjusted analyses, AMH levels >0.7 ng/mL (hazard ratio, 2.9; 95% confidence interval, 1.5‐5.6) and FSH levels ≤10 IU/L (hazard ratio, 4.7; 95% confidence interval, 1.3‐16.8) were associated with a shorter time to ovarian recovery, whereas inhB levels were not related. A prognostic score based on age <40 years, AMH >0.7 ng/mL, and body mass index ≥25 kg/m2 was used to estimate the timing of recovery. CONCLUSIONS In reproductive‐aged women with newly diagnosed breast cancer, prechemotherapy AMH and FSH levels were associated with the return of ovarian function, independent of age. A novel prognostic score incorporating AMH, age, and body size was capable of estimating the time to ovarian recovery. Pending validation, these data support using prechemotherapy ovarian reserve measures, particularly AMH, to prospectively counsel young patients on future ovarian function. Because ovarian function is not equivalent to fertility, follow‐up studies on predicting fertility are needed. Cancer 2014;120:3691–3698. © 2014 American Cancer Society.